Eksekusi Objek Jaminan Fidusia Pasca Putusan Mahkamah Konstitusi Republik Indonesia Nomor 18/PUU-XVII/2019 JUNCTO 02/PUU-XIX/2021 (Studi Kasus Pengadilan Negeri Medan) - Karna, Etha Pricilla; Kamelo, Tan; Sutiarnoto, Sutiarnoto; Yerfizawati, Yerfizawati (Journal of Law & Policy Review, 2023)
Fiduciary Security is a specific property guarantee granting creditors exclusive rights, including the ability to sell the collateral without a court order, known as parate execution, in the event of default. The execution of Fiduciary Security is governed by Law Number 42 of 1999 concerning Fiduciary Security, Article 15. The Constitutional Court Decision Number 18/PUU-XVII/2019 JUNCTO 02/PUU-XIX/2021 resulted from a constitutional review petition against Article 15 Paragraphs (2) and (3) of the law, leading to legal changes in the regulation and implementation of Fiduciary Security execution procedures. This study focuses on whether the decision aligns with Indonesia's legal system, the pre- and post-decision execution processes, and the legal analysis by judges at the Medan District Court. Using a normative juridical method, this research concludes that the Constitutional Court Decision provides a new interpretation of executory titles and breach of promise. Before the decision, creditors held executory titles during Fiduciary Security execution upon debtor breach, but post-decision, mutual consent between creditors and debtors is required. Challenges in implementing the decision in the Medan District Court arise from societal and cultural factors.